2023
DOI: 10.1101/2023.05.07.539224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular visualization of G-quadruplex RNA via fluorescence lifetime imaging microscopy

Abstract: Over the last decade, appreciation of the potential roles of G-quadruplex (G4) structures in cellular regulation and maintenance have rapidly grown, making the establishment of robust methods to visualize G4s increasingly important. Fluorescent probes are commonly used for G4 detection in vitro, however, achieving sufficient selectivity to detect G4s with confidence in a dense and structurally diverse cellular environment is challenging. The use of fluorescence probes for G4 detection is further complicated by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Considering the large fluorescence response of QCy­(BnBT) 3 with the addition of RNA G4 sequences (Figure S8), it can be concluded that QCy­(BnBT) 3 might stain both DNA G4 and RNA G4 in cells with NIR fluorescence. Since similar fluorescence microscopic images were also reported in the case of the other fluorescent small molecular probes, ,, our results are reliable.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Considering the large fluorescence response of QCy­(BnBT) 3 with the addition of RNA G4 sequences (Figure S8), it can be concluded that QCy­(BnBT) 3 might stain both DNA G4 and RNA G4 in cells with NIR fluorescence. Since similar fluorescence microscopic images were also reported in the case of the other fluorescent small molecular probes, ,, our results are reliable.…”
supporting
confidence: 88%
“…The Stokes shift of the fluorescent G4 probe, QCy­(BnBT) 3 , reached ca. 220 nm, which is one of the largest Stokes shifts not only among the reported G4 binding fluorescent probes but also among the reported fluorophores. , The highly selective NIR fluorescence response of QCy­(BnBT) 3 upon the binding with G4 nucleic acids was observed both in the case of the test tube and in the cells, suggesting that the highly selective G4 imaging in the cells can be realized by using QCy­(BnBT) 3 . Since the highly selective ligand for G4 nucleic acids is one of the most important developmental targets in the field of chemical biology , and drug discovery, , our strategy described here would contribute greatly to researchers working in these fields.…”
mentioning
confidence: 95%
“…6 Fluorogenic aptamers have been used in diverse cellular imaging studies, including multi-color RNA imaging and single-molecule spectroscopy. 10,11,12,13,14 In addition to their use as imaging agents, uorogenic aptamers have been leveraged to create sensors. 15,16 The fact that these aptamers are genetically encodable, coupled with exibility in choicd of excitation-emission wavelengths makes them powerful tools for diverse applications.…”
Section: Introductionmentioning
confidence: 99%